Diversity in freshwater scuticociliates (Alveolata, Ciliophora, Scuticociliatia): Two new species isolated from a wetland in northern China, focusing on their morphology, taxonomy, and molecular phylogeny, with establishment of a new family Glauconematidae fam. nov. - Tao Li; Mingjian Liu; Jiachen Zhang; Khaled A.S. Al-Rasheid; Zigui Chen; Weibo Song; Hunter N. Hines; Zhe Wang (Water Biology and Security, 2024)
In the aquatic microbial food web, scuticociliates are diverse and predominant in almost all kinds of biotopes while extremely confused regarding their taxonomy and systematic relationships within the subclass Scuticociliatia. Here we provide detailed descriptions of two new and one known species, Glauconema sinica sp. nov., Pleuronema parasetigerum sp. nov., and Histiobalantium natans viridis, isolated from a freshwater wetland in northern China, along with their molecular phylogeny based on SSU rRNA gene sequences. Our results show: (1) both molecular and morphological data strongly support that the isolated lineage containing the genera Glauconema, Miamiensis, Paramesanophrys, and Anophryoides should be identified as a new taxon at the family level in the order Philasterida; hence, a new family, Glauconematidae fam. nov., is established. This new family is mainly characterized by the polymorphic life cycle of its members (macrostome and microstome stages); the trophont (or macrostome) has closely spaced membranelles 1–3, whereas in the tomite (or microstome) membranelle 1 is distant from membranelle 2. (2) Phylogenetic analyses using novel data for these species revealed that all three cluster with their congeners, supporting the validity of the genera to which they belong. Molecular information also supports the monophyly of the two main scuticociliate orders Pleuronematida and Philasterida.